Occurrence of polyglucosan bodies in temporal lobe epilepsy. Issue 11 (November 1992) - Loiseau, H; Marchal, C; Vital, A; Vital, C; Rougier, A; Loiseau, P
Abstract : Massive occurrence of polyglucosan bodies (PBs) was found within the surgically removed temporal lobe of a 34 year old woman with complex partial seizures. This peculiar feature is very unusual in neuropathological examinations of epileptogenic foci. This patient could not be included in any of the classic diseases in which PBs are found. She exhibited a localised form of glycogen storage disease.